Phylogenomic insights into West Nile virus lineage 2 circulating in Croatia - Barbara Anđelić Dmitrović; Kristian Bodulić; Ivan-Christian Kurolt (Virology Journal)
Abstract West Nile Virus (WNV) has been circulating in Croatia for over a decade, as well as in numerous countries across the Mediterranean Basin and Central Europe. Using high-throughput Illumina sequencing, we successfully sequenced the WNV genome from serum and urine samples of three Croatian patients infected in 2016, 2023 and 2024. We employed an amplicon-based approach, with optimized primers designed using previously published WNV lineage 2 sequences. This work represents the first report of complete WNV genome sequences from Croatia. Sequenced genomes from 2023 to 2024 exhibited 99% sequence identity with Hungarian genomic sequences, while the genome from 2016 showed 99% identity with genomic sequences from Austria and Czech Republic. Phylogenetic analysis supported these findings, placing the genomes from 2023 to 2024 in subclade D.2.1 and the genome from 2016 in subclade E.2, thereby providing evidence for potential viral dissemination routes. The approach employed in this study performed well in whole-genome assembly of WNV and in identifying nucleotide changes specific for WNV subtypes circulating in Croatia. This study offers deeper genomic insights into the phylogenetic position of WNV in Croatia, bridging a significant knowledge gap and contributing to future studies on WNV transmission dynamics.